1991
DOI: 10.1103/physrevd.43.369
|View full text |Cite
|
Sign up to set email alerts
|

Model dependence of the cosmological upper bound on the Higgs-boson mass

Abstract: We consider an electroweak scenario for baryon asymmetry generation in an extended model with two Higgs doublets. The upper bound on the mass of the lightest Higgs boson is obtained. It is shown to coincide with that of the theory with one Higgs doublet, namely, m, < m,, --45 GeV, if the masses of all Higgs bosons do not exceed the mass of the Wboson substantially. Otherwise the upper bound is shown still to exist but is greater than m,, and depends on the actual values of the scalarfield self-coupling constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 24 publications
0
85
0
Order By: Relevance
“…Their contributions to the effective Higgs potential can strengthen the PT and in addition introduce new sources of CP violation. Previous studies have shown that 2HDMs provide a good framework for successful baryogenesis [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (see [48][49][50][51][52] for studies in the CP-violating 2HDM).…”
Section: Jhep02(2017)121mentioning
confidence: 99%
“…Their contributions to the effective Higgs potential can strengthen the PT and in addition introduce new sources of CP violation. Previous studies have shown that 2HDMs provide a good framework for successful baryogenesis [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (see [48][49][50][51][52] for studies in the CP-violating 2HDM).…”
Section: Jhep02(2017)121mentioning
confidence: 99%
“…Once the temperature drops below the critical one T < T c , bubbles of true vacuum (φ c = 0) start to nucleate where the rate is suppressed as Γ ∼ exp (−E sph /T ). The sphaleron decoupling condition indicates that the rate of baryon number violation must be much smaller than the the Hubble parameter [8,9,43,44] and therefore, the…”
Section: Sphaleron Decoupling Conditionmentioning
confidence: 99%
“…Conventionally, the amount of BAU is calculated via the following relation, 5) where N f is the number of flavors in the model. The sphaleron rate, Γ sph , is defined as Γ sph = K(α W T ) 4 in the symmetric phase.…”
Section: Jhep11(2016)065mentioning
confidence: 99%
“…If the phase transition is strongly first order, the baryon violating processes are out of equilibrium in the bubble walls and a net baryon number can be generated during the phase transition. Phase transition is strong enough when [38][39][40],…”
Section: The Cp Violating Vacuummentioning
confidence: 99%
See 1 more Smart Citation